2005
DOI: 10.1007/s11095-005-2485-y
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Frontal Analysis of the Binding of Thyroxine Enantiomers to Human Serum Albumin Binding of Thyroxine Enantiomers to Human Serum Albumin Kimura

Abstract: Both enantiomers were bound to human serum albumin at two high-affinity sites with similar affinities. The binding constant (K) and the number of binding sites on an HSA molecule (n) evaluated from Scatchard plot analysis were K = 1.01 x 10(6)m(-1) and n = 1.90 for L: -thyroxine, and K = 9.71 x 10(5) m(-1) and n = 1.97 for D: -thyroxine. The binding sites were identified using phenylbutazone and diazepam as site-specific probes for sites I and II, respectively, and each enantiomer was found to bind to both sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Bilirubin, phenylbutazone, warfarin, and dansylamide bind on the Suddlow site I of HSA, whereas dansylproline, ibuprofen, or L-tryptophan bind on the Suddlow site II 7,26−28 and thyroxine binds on both sites. 29 It thus seems that the influence of the NEG of HSA on its binding capacity does not depend on the localization of the binding region, as it was already shown by the study of Koyama et al 8 This is confirmed by our study because 1 binds on the Suddlow site I of HSA, 2 binds on the Suddlow site II, and 3 has its primary binding site on the Suddlow site II and a weaker binding site on the Suddlow site I. 13,15 The difference in the influence of NEG on the binding affinity of HSA for the three studied contrast agents could thus be explained by the different structures of the gadolinium complexes and hence their affinity for HSA.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Bilirubin, phenylbutazone, warfarin, and dansylamide bind on the Suddlow site I of HSA, whereas dansylproline, ibuprofen, or L-tryptophan bind on the Suddlow site II 7,26−28 and thyroxine binds on both sites. 29 It thus seems that the influence of the NEG of HSA on its binding capacity does not depend on the localization of the binding region, as it was already shown by the study of Koyama et al 8 This is confirmed by our study because 1 binds on the Suddlow site I of HSA, 2 binds on the Suddlow site II, and 3 has its primary binding site on the Suddlow site II and a weaker binding site on the Suddlow site I. 13,15 The difference in the influence of NEG on the binding affinity of HSA for the three studied contrast agents could thus be explained by the different structures of the gadolinium complexes and hence their affinity for HSA.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Based on their observation HAS-based chiral stationary phases were developed for the enantioseparation of tryptophan, ibuprofen, warfarin etc. HSA was immobilized on membranes for enantioseparation of ibuprofen [108]. The protein-immobilized enantioselective ceramic membranes were prepared by chemically immobilizing bovine serum albumin by glutaraldehyde linkage on the surface of a porous ceramic membrane.…”
Section: Optical Resolution Through Chiral Membranesmentioning
confidence: 99%
“…In the present work, l -thyroxin, a thyroid hormone which is known to bind to thyroxin binding globulin (TBG) ( K a = 9.08 ± 0.62 × 10 9 M −1 with n ∼ 1 at 310 K), transthyretin (TTR) ( K a = 1.3 × 10 7 M −1 with n ∼ 1 at 310 K), and HSA ( K a = 1.01 × 10 6 M −1 with n = 1.9 at 310 K), was coupled to a derivative of Gd-DTPA carrying a p -isothiocyanatobenzyl substituent. The resulting complex, Gd-C 4 -thyroxin-DTPA (Figure ), was then characterized in aqueous solution and in the presence of human serum albumin.…”
Section: Introductionmentioning
confidence: 99%